‘Here gather daily those young eaglets of glory’: Robert Louis Stevenson, the Savile Club and the Suicide Club - Robert-Louis Abrahamson (Cahiers Victoriens et Edouardiens)
The Savile Club prided itself in being more relaxed and friendly than most other gentlemen’s clubs in London in the second half of the nineteenth century, welcoming ‘men of promise’ at the start of their careers. Robert Louis Stevenson, one of these young men of promise, relished the social opportunities of the club, especially the company of fellow bohemians but was also aware of the limitations of the club, and its potential for complacency and false posturing. His novella ‘The Suicide Club’, depicting a club similar to the Savile, satirises the artificiality of the club, and of all such clubs, and of the superficial respectability of the members’ bohemian pretensions, which shelter the ‘gentlemen’ from a genuine and fulfilling engagement in the battlefield of life.